Effect of family-centered empowerment model on quality of life in adults with chronic diseases: A systematic review and meta-analysis study - Amir Vahedian-Azimi; Farshid Rahimi Bashar; Hosein Amini; Mahmood Salesi; Fatemeh Alhani (Tehran University of Medical Sciences, 2018)
Background & Aim: Empowerment is a dynamic, positive, interactive and social process, leading to the improvement of quality of life (QOL) in patients with chronic disease. The purpose of this systematic review and meta-analysis was to determine the effect of family-centered empowerment model (FCEM) on QOL in adults with chronic diseases. Methods & Materials: By searching FCEM in Persian databases including SID, MagIran, IranMedex, IranDoc, and googlescholar, Scopus, Pubmed, Web-of-science, Proquest, and Sciencedirect, all relevant studies were extracted. The methodological quality of the papers was examined using Cochrane-risk-of-bias. Data analysis was carried out through the random effects model and heterogeneity by I2 index. The data were analyzed using the STATA software version 11.0. Results: Of the 647 initial studies, only 8 studies examined the effect of FCEM on the QOL in adult patients using SF-36. The pooled standardized mean difference of the 8-dimensions of QOL included: social-functioning (1.781), Physical role limitation (1.416), bodily pain (0.987), general health (1.352), social functioning (1.010), general health (1.122), emotional role limitation (0.656), and vitality (1.361). Conclusion: The implementation of FCEM had a significant effect on the 8-dimensions of QOL based on the SF-36 questionnaire. The implementation of FCEM is recommended in order to improve the QOL of adult patients with chronic disease.